Production of cellulase enzyme from oil palm empty fruit bunch (OPEFB) by Trichoderma Reesei Rut C-30 using solid state fermentation - Manisya Zauri binti Abdul Wahid (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Vast quantities of oil palm empty fruit bunches (OPEFB) are being produced during processing of oil palm in the oil palm industry. The OPEFB posses a pollution problem to the environment. The study focusses on the production of cellulases from oil palm empty fruit bunches (OPEFB) by solid state fermentation using commercial strain Trichoderma reesei RUT C-30 has been carried out using several approaches. The ability of Trichoderma reesei RUT C-30 to produce cellulases on CMC agar and SSF of OPEFB particles in culture flask were compared to Penicillium (2 strains) and Trichoderma harzianum (2 strains) from the culture collection stock of Environmental Biotechnology Laboratory, IIUM. Trichoderma reesei RUT C-30 and strain Penicillium 1 gave high cellulolytic activity on day 2 and day 3 of growth culture, respectively, by forming clearing zones on the CMCase agar that has been stained with 1 mg/ml of congo red dye solution. However, Trichoderma reesei RUT C-30 produced the highest cellulases production from OPEFB under SSF culture flask compared to other tested strains with maximum CMCase, FPase and β-glucosidase production values of 1.831, 0.111 and 2.361 U/gds, respectively. The characterization of OPEFB fibres contained 49.2, 25.9 and 17.3 % of cellulose, lignin and hemicelluloses, respectively. On CMCase activity by Trichoderma reesei RUT C-30 using different OPEFB particle sizes of 0.105-0.225 mm, 0.225-425 mm, 0.425-0.6 mm and 0.6–0.816 mm showed that using OPEFB particle size of 0.225-0.425 mm gave the highest CMCase activity with the value of 1.782 U/gds. The effect of pretreatment of the OPEFB particles (0.225-0.425 mm) with various concentrations of acid (1-3 N) or alkali (1-15 N) followed by autoclaving at different steaming time (10-30 min) on the cellulose, lignin and hemicelluloses content of the OPEFB particles was studied. The study found 58.4 % of cellulose was recovered from OPEFB soaked for 1h with 3N of HCl followed by autoclaving for 10 min. Furthermore, 99.2 % of hemicelluloses were recovered on the OPEFB fibers that have been soaked in 3N of HCl for 1h followed by 20 min of autoclaving. Meanwhile, the OPEFB particles treated with more concentrated alkali (15 N NaOH) followed by autoclaving for 20 min was able to remove 36.8 % of OPEFB lignin. All the pretreated OPEFB particles have not shown any apparent surface changes when examined under SEM micrograph. Result on untreated OPEFB particles were found to produce higher cellulases activities by Trichoderma reesei RUT C-30 compared to pretreated OPEFB particles. A total of 11 parameters comprising various concentration of peptone, urea, ammonium sulfate, calcium nitrate, yeast extract, tween 80, pH, incubation time, initial moisture content, inoculum size and substrate amount was screened for significant parameters affecting cellulase enzymes production. It was found that factors of initial moisture content (P>F=0.001), incubation time (P>F=0.001), inoculum size (P>F=0.023) and ammonia sulfate concentration (P>F=0.032) significantly affect cellulases production. The optimization of these parameters improved CMCase yield with maximum production of 5.341 U/ml with productivity of 1.22 U/mg/min glucosamine being obtained. It was found with ammonium sufate concentration, initial moisture content and inoculum density of 132 mg/L, 60 % and 1x107 spores/ml, respectively, gave high yield of celluase at day 11 of the grown culture in SSF. The cellulases of the collected filtrate crude sample were characterized based on temperature, pH, substrate concentration and incubation time. Results indicate that endoglucanase (CMCase), exoglucanase (FPase) and β-glucosidase of the collected filtrate crude sample were stable at pH between 4 and 8. CMCase and FPase were found to be stable at temperature range of between 600C and 800C compared to β-glucosidase which has lower optimum stability temperature between 300C and 500C. The kinetic investigation on each of the